Chair - Loizou, Christos P. (My University, 2026)
E. Ambrosini1, M. Caielli1, M. Milis, C. P. Loizou, et al., “Automatic speech analysis to early detect cognitive impairment in elderly population”, 41st Ann. IEEE Int. Conf. Eng. Medic. Biol. Society (EMBC), pp. 12-16, Berlin, Germany, 23-27 July, 2019.